Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/apa.13165
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory illness contributed significantly to morbidity in children born extremely premature or with extremely low birthweights in 1999–2000

Abstract: Respiratory morbidity decreased during the first five years of life but was still more common than expected. It was unrelated to BPD and gestational age at five years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Pulmonary abnormalities after EP birth may clinically mimic pediatric asthma, and studies have reported increased respiratory symptoms and more hospital admissions, particularly during the first few years of life [ 33 35 ]. In this group of 11 year old children born EP in 1999–2000, current respiratory symptoms and use of asthma medication were reassuringly rare, also in those who were most immature at birth, contrasting some previous studies (8, 12, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary abnormalities after EP birth may clinically mimic pediatric asthma, and studies have reported increased respiratory symptoms and more hospital admissions, particularly during the first few years of life [ 33 35 ]. In this group of 11 year old children born EP in 1999–2000, current respiratory symptoms and use of asthma medication were reassuringly rare, also in those who were most immature at birth, contrasting some previous studies (8, 12, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Although respiratory symptoms in EPT-born children resemble asthma, the pathophysiology of lung disease after preterm birth is different which, for instance, is reflected in that the disease is unresponsive to inhaled corticosteroids 12 40–42. Their burden of respiratory symptoms may therefore be substantially higher, and more chronic16 and therefore more easily overlooked. For example, it is conceivable that poor sleep due to respiratory problems may cause daytime sleepiness and contribute to inattention and learning difficulties which are major challenges for children born EPT 43 44.…”
Section: Discussionmentioning
confidence: 99%
“…EPT was defined as gestational age (GA) <28 completed weeks or birth weight (BW) <1000 g. The children were prospectively followed from birth and assessed at 2, 5 and 11 years of age. Method for determination of GA and overall outcome in terms of mortality and morbidities until 11 years have been published previously 9 13–16. At 11 years, we obtained information on the families’ sociodemographic characteristics and lifestyles, and the children’s health, including sleep characteristics, behavioural issues and respiratory health, from postal questionnaires completed by the parents (for behaviour also the children’s teacher).…”
Section: Methodsmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) was defined as still dependency on oxygen supplementation at 36 weeks' GA. The respiratory medical history of this cohort has been published (20,33). PDA was diagnosed at the discretion of the participating NICUs, with algorithms based on echocardiographic assessment of the left atrium to the aortic root ratio (above 1.3-1.5 depending on clinical situation) and clinical signs as listed by Evans in 1993 (bounding hyper dynamic pulses and signs of cardiac or respiratory insufficiency) (34).…”
Section: Sources and Collection Of Datamentioning
confidence: 99%